L-tryptophan functionalized NH2 -UiO-66(Zr) crosslinked with glutaraldehyde adsorbent for sensitive detection and effective removal of mercury (II) - Nadia H. Elsayed; Nawaa Ali H. Alshammari; Maymounah N. Alharthi; Raedah A.S. Alatawi; Abeer Abdulaziz H. Bukhari; Ali Hamzah Alessa; Menier Al-Anazi; M.A.M. El-Afify (Journal of Water Process Engineering, 2026)

Breaking a mitochondrial danger–STING feed-forward amplifier preserves alveolar–capillary architecture and dampens interferon–chemokine signaling in acute lung injury - Elsayed A. Elmorsy; Maha M. Amer; Rabab S. Hamad; Mohamed R. Abdel-Hamed; Alshaimaa A. Farrag; Mohammed Alorini; Mostafa M. Khodeir; Mohamed A.M. Ali; Ahmad H. Alhowail; Enas A. Mohamed; Abdulaziz A. Alsalloom; Hamad Alsaykhan; et al. (Tissue and Cell, 2026)

Effect of Beet Molasses Application On Wheat (Triticum aestivum L.) Germination and Seedling Growth Under Salinity Stress - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Metwaly Mahfouz Salem Metwaly; Hosny H. Kesba; Rania Anwar Khedr; Mohamed M. El-Mogy; Elsayed Abd Elmaksoud Abomarzokae; Wael Elmenofy; Khloud Ali Hamza (Journal of Crop Health, 2026)

Adenosine A₂A receptor as a dual-acting molecular switch: Glial morphological changes and neurovascular tissue remodeling in neuroinflammation and neurodegeneration - Heba Ibrahim Abd El-Moaty; Ahmed Sameh; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Norah Suliman Alsoqih; Alshaimaa A. Farrag; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; et al. (Tissue and Cell, 2026)

A self-organized fuzzy neural model for the pressurizer system in nuclear power plants - Elsayed H. Ali; Amal A. Sheta; Sayed M. El-Araby; Mohammed I. Mahmoud; Tarek A. Mahmoud (Annals of Nuclear Energy, 2026)

Arbuscular mycorrhizal fungi confers resistance to Macrophomina phaseolina in coriander under different nitrogen fertilizer rates - Marzouk R. Abdel-Latif; Abdelrazek S. Abdelrhim; Ranya M. S. El-Ashmony; Yasmin M. R. Abdellatif; Hanaa A. H. Armanious; Ismail A. A. Tantawy; Mahmoud Elsayed; Abeer S. Alqurashi; Hatim M. Al-Yasi; Esmat F. Ali; Abdelmonim Ali Ahmad (Journal of Plant Pathology, 2026)

Evaluation of lactoferrin administration as an antibiotic alternative growth promoter: impacts on rabbit’s growth, meat quality, blood biochemical parameters, immune status, antioxidant status, and tissue histology - Tharwat A. Imbabi; Shimaa A. Amer; Eman H. Halawa; Islam I. Sabeq; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Shimaa N. Edris; Simon J. Davies; Lamiaa M. El-Maghraby; Abdalla El-Hadary; Ebrahim Elkhtab; Mohamed H. Abdel Aal; et al. (Tropical Animal Health and Production, 2025)

The impacts of novel lyophilized milk fermented with potential probiotic Lactobacillus sp. on the physiological indicators, meat characteristics, blood parameters, and gene expression in weaned rabbits - Ebrahim Elkhtab; Ali Osman; Rania M. Y. Heakel; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ahmed A. Aly; Mohamed H. Abdel Aal; Islam Sabeq; Shimaa A. Amer; Simon J. Davies; Tharwat A. Imbabi (Tropical Animal Health and Production, 2025)

Reprogramming the hepatic immune microenvironment with mirtazapine in early neoplastic transformation: Evidence from a diethylnitrosamine-induced rat model - Elsayed A. Elmorsy; Sameh Saber; Ahmad H. Alhowail; Abousree T. Ellethy; Enas A. Mohamed; Hamad Alsaykhan; Hatim Y. Alharbi; Omar Almansour; Abdelrahman El-Sayed; Manal Mohamed Hatem; Ahmed Kaid Alantry; Walaa A. Allam; et al. (Chemico-Biological Interactions, 2025)

Nutrient therapies: Boosting plant immunity for a sustainable future - Mohamed S. Attia; Amer M. Abdelaziz; Mostafa I. Abdelglil; Amr H. Hashem; Eslam K. Kandil; Eslam O. Elsawwah; Mohammed S. Helal; Salah M. Elsayed; Mustafa A. Nouh; Maryam M. Elsayed; Mohamed M. Ali; Mohamed Soliman Dora; et al. (Physiological and Molecular Plant Pathology, 2025)

Tailored ion-imprinted polymer for europium(III) recovery: A cellulose-based click chemistry approach - Nadia H. Elsayed; Duna A.K. Alenazi; Kholoud M. Alnahdi; Shareefa Ahmed Alshareef; Menier Al-Anazi; Nawaa Ali H. Alshammari; Maha Ali Aljowni; Raedah A.S. Alatawi; Abeer Abdulaziz H. Bukhari; Jawza Sh. Alnawmasi; Yasmeen G. Abou El-Reash; M. Monier; et al. (Journal of Water Process Engineering, 2025)

The Role of MicroRNAs in Neurodegeneration: Insights from Huntington’s Disease - Reda M. Mansour; Abanoub A. S. Shaker; Ahmed I. Abulsoud; Sherif S. Abdel Mageed; Alaa Ashraf; Elsayed G. E. Elsakka; Mohammed. I. Dahab; Mohamed M. Sadek; Farah A. Awad; Radwa H. Lutfy; Hanan Elimam; Ahmed H. I. Faraag; et al. (Molecular Neurobiology, 2025)

The impact of betalains and organic selenium on the physiological responses, blood metabolites, redox status, and semen quality of heat-stressed rabbits - Tharwat A. Imbabi; Eman H. Halawa; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Dina A. Selim; Mohamed H. Abdel Aal; Lamiaa M.M. EL-Maghraby; Abdalla El-Hadary; Shimaa A. Amer; Simon J. Davies; Mohamed S. Basiouny; Mahmoud Sitohy; et al. (Animal Feed Science and Technology, 2025)

Malfunction diagnosis based on residence time distribution of radiotracer signals in industrial processes using machine learning techniques - Mohamed S. El_Tokhy; H. Kasban; Elsayed H. Ali (Annals of Nuclear Energy, 2025)

Efficient adsorption of fluorescein dye from aqueous solutions by Al/Th-MOF bimetal-organic frameworks: Adsorption isotherm, kinetics, DFT computation, and optimization via Box-Behnken design - Nawaa Ali H. Alshammari; Jawza Sh Alnawmasi; Alya M. Alotaibi; Odeh A.O. Alshammari; May Abdullah Abomuti; Nadia H. Elsayed; Ashraf A. El-Bindary (Process Safety and Environmental Protection, 2024)

Genotype classification and pathogenicity of infectious bursal disease virus circulating in vaccinated broiler chicken farms - Samah M. Mosad; Mona M. Elsayed; Enas M. Hammad; Basma M. Hendam; Hanaa S. Ali; Abdelfattah H. Eladl; Mohamed A. Saif (Veterinary Research Communications, 2024)
This study investigated the genotype classification and pathogenicity of infectious bursal disease virus (IBDV) circulating in vaccinated broiler chicken farms in Egypt. A total of 150 samples were collected from 30 vaccinated commercial broiler chicken farms and pooled into 30 working samples. IBDV was tested using reverse transcriptase polymerase chain reaction (RT-PCR) amplification of the hypervariable region of the viral protein 2 (hvVP2) and the VP1 gene 5’ extremity. Both RT-PCR fragments were sequenced from six samples, and then the obtained nucleotide sequences were analyzed. The IBDV genotypes were identified using nucleotide sequences. Five sequences of the six strains examined were classified as genotype A3B2 for the highly virulent segments A and B (vv-A/vv-B IBDV). Interestingly, this study identified and classified a novel segment-reassortant strain as the A1B2 genotype. Specifically, it involved the segment reassortment of classical virulent segment A (cv-A) with vv-B producing cv-A/vv-B reassortant IBDV. Subsequently, we compared the pathogenicity of reassortant (cv-A/vv-B) IBDV and vvIBDV strains identified in this study. Both strains developed typical IBD clinical signs, postmortem lesions, histopathology, immunohistochemistry, and lesion scores, which were more severe in vvIBDV than reassortant IBDV. In conclusion, this is the first report of the genotype classification based on both genome segments (hvVP2 and VP1) with pathogenicity of IBDV circulating in vaccinated broiler chicken farms and this pathogenicity is more severe in vvIBDV strain than a novel reassortant IBDV strain.

Effect of intermittent fasting on adriamycin-induced nephropathy: Possible underlying mechanisms - Fathy H. Elsaid; Abdelaziz M. Hussein; Elsayed A. Eid; Omar A. Ammar; Ali Ali Khalil (Tissue and Cell, 2024)

Development of high-resolution gridded data for water availability identification through GRACE data downscaling: Development of machine learning models - Hai Tao; Ahmed H. Al-Sulttani; Sinan Q. Salih; Mustafa K.A. Mohammed; Mohammad Amir Khan; Beste Hamiye Beyaztas; Mumtaz Ali; Salah Elsayed; Shamsuddin Shahid; Zaher Mundher Yaseen (Atmospheric Research, 2023)

Correction to: The protective role of iodine and MS‑222 against stress response and bacterial infections during Nile tilapia (Oreochromis niloticus) transportation - Ahmed H. Sherif; Elsayed A. Eldessouki; Nader M. Sabry; Nadia G. Ali (Aquaculture International, 2023)

Path toward sustainable desalination: Sodium precipitation and carbon capture - Ahmed Elsayed; Ali H. Al-Marzouqi (Desalination, 2023)

The protective role of iodine and MS-222 against stress response and bacterial infections during Nile tilapia (Oreochromis niloticus) transportation - Ahmed H. Sherif; Elsayed A. Eldessouki; Nader M. Sabry; Nadia G. Ali (Aquaculture International, 2023)
Fish transportation is a regular farming and experimental practice that mainly results in stress conditions that may extend to induce a high mortality rate. In the present experimental simulation, Oreochromis niloticus were transported for 2 h and maintained for another 6 h in transportation containers to assess the effect of tranquilization with tricaine methanesulfonate (MS-222) and/or the addition of iodine on mortality rate and restoring the normal physiological functions. Experimental fish were divided into four groups: group 1 (control) was transported in farm water without MS-222 or iodine, group (2) was transported in farm water supplemented with 40 mg/L of MS-222, fish in group (3) were transported in farm water supplemented with 40 mg/L of MS-222 + 10 ppm iodine, and fish in group (4) were transported in farm water containing 10 ppm iodine. Blood samples were collected for the determination of serum cortisol and glucose, while skin mucus was collected for assaying lysozyme, peroxidase and antibacterial activity; cumulative mortality rate; and food reflexes which were assessed at 0 h, 1 h, 6 h, 48 h, 7 days and 14 days post 2 h transportation. The results indicated that fish tranquilization with MS-222 and/or treatment with iodine mitigated the stress condition associated with transportation and accelerate restoration of the normal physiological and immunological status. So, it was recommended to use the MS-222 as a tranquillizer together with iodine as an antiseptic during transportation of O. niloticus .

Co-digestion of cow manure and food waste for biogas enhancement and nutrients revival in bio-circular economy - Yasir Abbas; Sining Yun; Ayaz Mehmood; Fayyaz Ali Shah; Kaijun Wang; Elsayed Tag Eldin; Wahidah H. Al-Qahtani; Shafaqat Ali; Patrizia Bocchetta (Chemosphere, 2023)

Environmental Assessment of Potentially Toxic Elements Using Pollution Indices and Data-Driven Modeling in Surface Sediment of the Littoral Shelf of the Mediterranean Sea Coast and Gamasa Estuary, Egypt - Magda M. Abou El-Safa; Salah Elsayed; Osama Elsherbiny; Adel H. Elmetwalli; Mohamed Gad; Farahat S. Moghanm; Ebrahem M. Eid; Mostafa A. Taher; Mohamed H. E. El-Morsy; Hanan E. M. Osman; Ali H. Saleh (Journal of Marine Science and Engineering, 2022)
Coastal environmental assessment techniques have evolved into one of the most important fields for the long-term development and management of coastal zones. So, the overall aim of the present investigation was to provide effective approaches for making informed decisions about the Gamasa coast sediment quality. Over a two-year investigation, sediment samples were meticulously collected from the Gamasa estuary and littoral shelf. The inductively coupled plasma mass spectra (ICP-MS) was used to the total concentrations of Al, Fe, Ti, Mg, Mn, Cu, P, V, Ba, Cr, Sr, Co, Ni, Zn, Pb, Zr, and Ce. Single elements environmental pollution indices including the geoaccumulation index (Igeo), contamination factor (CF), and enrichment factor (EF), as well as multi-elements pollution indices comprising the potential ecological risk index (RI), degree of contamination (Dc), and pollution load index (PLI) were used to assess the sediment and the various geo-environmental variables affecting the Mediterranean coastal system. Furthermore, the Dc, PLI, and RI were estimated using the random forest (RF) and Back-Propagation Neural Network (BPNN) depending on the selected elements. According to the Dc results, all the investigated sediment samples categories were considerably contaminated. Cr, Co, Ni, Cu, Zr, V, Zn, P, and Mn showed remarkable enrichment in sediment samples and were originated from anthropogenic sources based on the CF, EF, and Igeo data. Moreover, the RI findings revealed that all the samples tested pose a low ecologically risk. Meanwhile, based on PLI, 70% of the Gamasa estuary samples were polluted, while 93.75% of littoral shelf sediment was unpolluted. The BPNNs -PCs-CD-17 model performed the best and demonstrated a better association between exceptional qualities and CD. With R2 values of 1.00 for calibration (Cal.) and 1.00 for validation (Val.). The BPNNs -PCs-PLI-17 models performed the best in terms of measuring PLI with respective R2 values of 1.00 and 0.98 for the Cal. and Val. datasets. The findings showed that the RF and BPNN models may be used to precisely quantify the pollution indices (Dc, PLI, and RI) in calibration (Cal.) and validation (Val.) datasets utilizing potentially toxic elements of surface sediment.

Environmental Pollution Indices and Multivariate Modeling Approaches for Assessing the Potentially Harmful Elements in Bottom Sediments of Qaroun Lake, Egypt - Ali H. Saleh; Mohamed Gad; Moataz M. Khalifa; Salah Elsayed; Farahat S. Moghanm; Adel M. Ghoneim; Subhan Danish; Rahul Datta; Moustapha E. Moustapha; Magda M. Abou El-Safa (Journal of Marine Science and Engineering, 2021)
This research intends to offer a scientific foundation for environmental monitoring and early warning which will aid in the environmental protection management of Qaroun Lake. Qaroun Lake is increasingly influenced by untreated wastewater discharge from many anthropogenic activities, making it vulnerable to pollution. For that, six environmental pollution indices, namely contamination factor (Cf), enrichment factor (EF), geo-accumulation index (Igeo), degree of contamination (Dc), pollution load index (PLI), and potential ecological risk index (RI), were utilized to assess the bottom sediment and to determine the different geo-environmental variables affecting the lake system. Cluster analysis (CA), and principal component analysis (PCA) were used to explore the potential pollution sources of heavy metal. Moreover, the efficiency of partial least-square regression (PLSR) and multiple linear regression (MLR) were tested to assess the Dc, PLI, and RI depending on the selected elements. The sediment samples were carefully collected from 16 locations of Qaroun Lake in two investigated years in 2018 and 2019. Total concentrations of Al, As, Ba, Cd, Co, Cr, Cu, Fe, Ga, Hf, Li, Mg, Mn, Mo, Ni, P, Pb, Sb, Se, Zn, and Zr were quantified using inductively coupled plasma mass spectra (ICP-MS). According to the Cf, EF, and Igeo results, As, Cd, Ga, Hf, P, Sb, Se, and Zr demonstrated significant enrichment in sediment and were derived from anthropogenic sources. According to Dc results, all collected samples were categorized under a very high degree of contamination. Further, the results of RI showed that the lake is at very high ecological risk. Meanwhile, the PLI data indicated 59% of lake was polluted and 41% had PLI